2019
DOI: 10.1371/journal.pntd.0007819
|View full text |Cite
|
Sign up to set email alerts
|

IL-4/IL-13 polarization of macrophages enhances Ebola virus glycoprotein-dependent infection

Abstract: BackgroundEbolavirus (EBOV) outbreaks, while sporadic, cause tremendous morbidity and mortality. No therapeutics or vaccines are currently licensed; however, a vaccine has shown promise in clinical trials. A critical step towards development of effective therapeutics is a better understanding of factors that govern host susceptibility to this pathogen. As macrophages are an important cell population targeted during virus replication, we explore the effect of cytokine polarization on macrophage infection.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 90 publications
0
27
0
1
Order By: Relevance
“…36 Peritoneal delivery of EBOV causes significant pathology in a variety of different animal models, [37][38][39] with pmacs as potential early targets of infection. 40,41 In these studies, we also extensively utilized a BSL-2 model virus of EBOV, recombinant vesicular stomatitis virus encoding EBOV glycoprotein and GFP in place of the native G glycoprotein (rVSV/EBOV GP). Our laboratory has previously found that rVSV/EBOV GP recapitulates many aspects of EBOV infection both in vitro and in vivo, including virus tropism and responsiveness to proinflammatory and anti-inflammatory cytokines during M infection.…”
Section: A Bsl-2 Model Virus Of Ebov Rvsv/ebov Gp Recapitulates Finmentioning
confidence: 99%
“…36 Peritoneal delivery of EBOV causes significant pathology in a variety of different animal models, [37][38][39] with pmacs as potential early targets of infection. 40,41 In these studies, we also extensively utilized a BSL-2 model virus of EBOV, recombinant vesicular stomatitis virus encoding EBOV glycoprotein and GFP in place of the native G glycoprotein (rVSV/EBOV GP). Our laboratory has previously found that rVSV/EBOV GP recapitulates many aspects of EBOV infection both in vitro and in vivo, including virus tropism and responsiveness to proinflammatory and anti-inflammatory cytokines during M infection.…”
Section: A Bsl-2 Model Virus Of Ebov Rvsv/ebov Gp Recapitulates Finmentioning
confidence: 99%
“…However, IL-4 has a dual role in viral infections due to two different haplotypes in the IL-4 gene. It can promote infections with the Herpes virus and the norovirus [ 43 ] as well as with the Ebola virus, which is related to the coronavirus [ 44 ]. On the other hand, IL-4 can also inhibit viral infections by promoting innate immunity [ 45 , 46 , 47 ].…”
Section: Type 2 Inflammation Blocking and Viral Infectionsmentioning
confidence: 99%
“…Rapid antiviral innate immunity may also be mediated by EBOV-GP, which has been shown to induce activation of human macrophages and DCs via TLR4 signaling [ 158 , 159 , 160 , 161 ]. This effect of membrane-bound GP (predominant form during vaccination) is distinct from the effects of soluble GP (sGP), which is produced in large quantities during EBOV infection: for instance, in vitro stimulation of DCs and macrophages with sGP thwarts migratory ability and induces a robust cytokine response while simultaneously increasing vascular permeability [ 4 , 162 , 163 ].…”
Section: Rvsv-ebov-gp and Rapid Protection: The Role Of Innate Immmentioning
confidence: 99%
“…This effect of membrane-bound GP (predominant form during vaccination) is distinct from the effects of soluble GP (sGP), which is produced in large quantities during EBOV infection: for instance, in vitro stimulation of DCs and macrophages with sGP thwarts migratory ability and induces a robust cytokine response while simultaneously increasing vascular permeability [ 4 , 162 , 163 ]. Whereas TLR4 stimulation has been shown to activate DCs and macrophages to differentiate and macrophages to polarize into an anti-inflammatory state [ 6 , 109 , 158 , 161 , 164 , 165 , 166 , 167 ]. Studies in mice demonstrate that vaccination with three doses of purified EBOV-GP confers partial protection (70% survival) from lethal EBOV infection in [ 157 ].…”
Section: Rvsv-ebov-gp and Rapid Protection: The Role Of Innate Immmentioning
confidence: 99%